2018
DOI: 10.1186/s40824-018-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in stem cell therapeutics and tissue engineering strategies

Abstract: BackgroundTissue regeneration includes delivering specific types of cells or cell products to injured tissues or organs for restoration of tissue and organ function. Stem cell therapy has drawn considerable attention since transplantation of stem cells can overcome the limitations of autologous transplantation of patient’s tissues; however, it is not perfect for treating diseases. To overcome the hurdles associated with stem cell therapy, tissue engineering techniques have been developed. Development of stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 74 publications
(63 reference statements)
0
101
0
1
Order By: Relevance
“…Since fibrin can be easily formed under physiological conditions and is characterized by both biocompatibility and cell adhesion, previous studies have reported that transplantation of ADSCs embedded in fibrin glue promotes regeneration through a neuroprotective effect on sensory neurons and stimulation of axon growth 16 . Although stem cell therapy provides a new paradigm in tissue regeneration, they are limitation in clinical application due to the poor survival and differentiation potentials of the transplanted cells 36 . Regarding PRFr, it has significant GF activity so that they can be administered with ADSCs to damaged tissues by either transplanting cells or, as a safer alternative, using the conditioned medium of ADSCs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Since fibrin can be easily formed under physiological conditions and is characterized by both biocompatibility and cell adhesion, previous studies have reported that transplantation of ADSCs embedded in fibrin glue promotes regeneration through a neuroprotective effect on sensory neurons and stimulation of axon growth 16 . Although stem cell therapy provides a new paradigm in tissue regeneration, they are limitation in clinical application due to the poor survival and differentiation potentials of the transplanted cells 36 . Regarding PRFr, it has significant GF activity so that they can be administered with ADSCs to damaged tissues by either transplanting cells or, as a safer alternative, using the conditioned medium of ADSCs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, and especially in the last decade, stem cell research has blossomed into an exciting and promising field. Stem cells, especially ESCs and iPSCs have shown great application promise in four major fields: regenerative and transplant medicine [11,12]; disease modeling [13,14]; drug discovery screening [15,16]; and human developmental biology [17] [18],. Thus, the evolution of regenerative medicine continues, from the early first descriptions of stem cells to their expanding clinical applications at present.…”
Section: Introductionmentioning
confidence: 99%
“…However, cell-based therapeutics face the challenges of low survivability and differentiation potential of transplanted cells. A tissue engineering approach, based on the combination of cells, biomaterials, and biochemicals, may be able to overcome these limitations [ 141 , 142 ]. As such, 3D cell printing is a powerful technology for constructing tissue-engineered tissue/organs.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%